Beispiel Nr: 02
$ \text{Gegeben:}\\\text{Hypotenuse} \qquad c \qquad [m] \\ \text{Kathete}\qquad b \qquad [m] \\ \\ \text{Gesucht:} \\ \text{Kathete} \qquad a \qquad [m] \\ \\ a =\sqrt{c^{2} - b^{2} }\\ \textbf{Gegeben:} \\ c=10m \qquad b=6m \qquad \\ \\ \textbf{Rechnung:} \\ a =\sqrt{c^{2} - b^{2} } \\ c=10m\\ b=6m\\ a =\sqrt{(10m)^{2} - (6m)^{2} }\\\\a=8m \\\\\\ \tiny \begin{array}{|l|} \hline c=\\ \hline 10 m \\ \hline 100 dm \\ \hline 10^{3} cm \\ \hline 10^{4} mm \\ \hline 10^{7} \mu m \\ \hline 0,01 km \\ \hline \end{array} \tiny \begin{array}{|l|} \hline b=\\ \hline 6 m \\ \hline 60 dm \\ \hline 600 cm \\ \hline 6\cdot 10^{3} mm \\ \hline 6\cdot 10^{6} \mu m \\ \hline 0,006 km \\ \hline \end{array} \tiny \begin{array}{|l|} \hline a=\\ \hline 8 m \\ \hline 80 dm \\ \hline 800 cm \\ \hline 8\cdot 10^{3} mm \\ \hline 8\cdot 10^{6} \mu m \\ \hline 0,008 km \\ \hline \end{array}$